O conceito de absoluto na filosofia de Friedrich W. J. Schelling - Jacob, Matheus Jalbut (2019)
This dissertation aims to explore Friedrich WJ Schelling's philosophy, in particular the concept of the Absolute in a specific period of his first philosophical phase, after his subjective philosophy, still influenced by Fichte's subjective idealism, and prior to the “second Schelling”, constantly focused on transforming the Catholicism on a viable philosophy. Throughout this dissertation, the reasons for Schelling's philosophy depreciation in the last centuries will be presented and discussed, as well as the reasons for his awakening on our current days. It will also be presented and analyzed the main philosophical roots of his Absolute, especially the works of Spinoza, Leibniz and Fichte. Finally, the present work analyzes Schelling's concept of Absolute in its original characteristics, with both his reality, expressed through the Naturphilosophie, and its ideality, as presented in the System of Transcendental Idealism, in addition to the Identity System, condition of unity and original and genetic identity of the duality presented in the Schellingian ideal-reality